Cross-Scale Systemic Resilience: Implications for Organization Studies. Issue 1 (January 2021) - Williams, Amanda; Whiteman, Gail; Kennedy, Steve
In this article, we posit that a cross-scale perspective is valuable for studies of organizational resilience. Existing research in our field primarily focuses on the resilience of organizations, that is, the factors that enhance or detract from an organization's viability in the face of threat. While this organization level focus makes important contributions to theory, organizational resilience is also intrinsically dependent upon the resilience of broader social-ecological systems in which the firm is embedded. Moreover, long-term organizational resilience cannot be well managed without an understanding of the feedback effects across nested systems. For instance, a narrow focus on optimizing organizational resilience from one firm's perspective may come at the expense of social-ecological functioning and ultimately undermine managers' efforts at long-term organizational survival. We suggest that insights from natural science may help organizational scholars to examine cross-scale resilience and conceptualize organizational actions within and across temporal and spatial dynamics. We develop propositions taking a complex adaptive systems perspective to identify issues related to focal scale, slow variables and feedback, and diversity and redundancy. We illustrate our theoretical argument using an example of Unilever and palm oil production in Borneo.